2021
DOI: 10.3892/ol.2021.13045
|View full text |Cite
|
Sign up to set email alerts
|

Maternally expressed 3 inhibits the biological activity of oral squamous cell carcinoma SCC25 and CAL27 cell lines

Abstract: The abnormal expression of long non-coding RNA (lncRNA) maternally expressed 3 (MEG3) is closely related to several tumor diagnosis and progression, such as endometrial carcinoma and ovarian cancer. However, the role of MEG3 in oral squamous cell carcinoma (OSCC) is rarely reported. The current study aimed to evaluate the expression of lncRNA MEG3 in OSCC tissues and cell lines and its effect on the biological behavior of OSCC cell lines. The expression of lncRNA MEG3 in the OSCC tissues and cell lines was det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…We found that GSK126 treatment indeed significantly inhibited H3K27me3 modification of the MEG3 gene locus and promoted MEG3 expression in OSCC cells, suggesting that the downregulation of MEG3 expression in OSCC cells was mediated by H3K27me3 modification of the MEG3 gene locus. Several reports have demonstrated that MEG3 inhibits proliferation, migration, invasion, and promotes apoptosis of OSCC cells [14][15][16]. In the present work, it was authenticated that overexpression of MEG3 resulted in the suppression of proliferation and invasion of OSCC cells, which is consistent with previous studies [14 -16].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…We found that GSK126 treatment indeed significantly inhibited H3K27me3 modification of the MEG3 gene locus and promoted MEG3 expression in OSCC cells, suggesting that the downregulation of MEG3 expression in OSCC cells was mediated by H3K27me3 modification of the MEG3 gene locus. Several reports have demonstrated that MEG3 inhibits proliferation, migration, invasion, and promotes apoptosis of OSCC cells [14][15][16]. In the present work, it was authenticated that overexpression of MEG3 resulted in the suppression of proliferation and invasion of OSCC cells, which is consistent with previous studies [14 -16].…”
Section: Discussionsupporting
confidence: 92%
“…MEG3 is usually acts as a tumor‐suppressive lncRNA, which is downregulated in tumor tissues and cells [ 9 , 10 , 11 , 12 , 13 ]. Several studies have shown that MEG3 expression is inhibited in OSCC tissues [ 14 , 15 , 16 ]. Consistent with this, we found that MEG3 expression was downregulated in OSCC tissues by analyzing TCGA data and the 72 pairs samples collected in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Combining HPA data and qPCR results, it was found that DCBLD1 proteins were moderately expressed in OSCC tissues but were absent in normal oral tissues. SCC25 and CAL27 cancer cell lines are derived from human OSCC commonly used in HNSCC studies (24), while gingival fibroblasts originated from the gingival tissues resected in normal people after the removal of impacted teeth. The qPCR results indicated that the expression of DCBLD1 mRNA in OSCC cells was higher than that in normal gingival fibroblasts, which further suggested that high DCBLD1 expression might associate with the development or progression of HNSCC.…”
Section: Discussionmentioning
confidence: 99%